Te hīnātore o te toroa = The light of the albatross : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters of Māori Visual Arts, Toioho ki Āpiti/Massey University, Palmerston North, New Zealand - Forde, Anton Sean (Massey University, 2019)
This thesis focuses on the Toroa/Albatross and its importance in Māori culture with particular reference to land markers, colonisation, Iwi Taranaki and Ngāti Porou. The research, methodology, and subsequent art practice has produced a body of significant and related works, which will be discussed. Through this research there have been relevant links made between the use of the feather and teardrop form in Māori culture. Pounamu and Tōtara are mediums that have mauri, and in turn are often associated with sacred rituals. The traditional and contemporary practices that are grounded in the connecting kōrero (stories) and forms are used as a basis for research and practice. The relationships between the Tītapu Toroa (Albatross feather) of Iwi Taranaki, the Roimata Toroa tukutuku of Ngāti Porou and the Tangiwai/Pounamu Roimata (teardrop) of Piopiotahi/ Milford Sounds are explored. The Toroa is the subject of many stories and artworks in Māori culture. This sacred bird is often portrayed as a guiding light for Māori and humanity as a whole, both historically and today. The importance of kaitiakiatanga (guardianship) of whenua (land), tangata (people), tikanga (cultural) practices in the korero (stories) of Toroa (Albatross), before and after colonisation, especially in the after effects as we see them today, will be explored. This enquiry has contextualised the use of Pounamu, Tōtara, Roimata and Tītapu make up the five works culminating in the exhibition Te Hīnātore o te Toroa - The light of the Albatross. There has been careful consideration in applying some of the knowledge acquired due to the tapu nature of these topics and the relevance of the exhibition taking place 250 years after Captain James Cook arrived in Aotearoa.
Some possibly copyrighted Figures are re-used under the "Fair dealing" principle for the purpose of criticism or review.
Keywords: 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)